Patient-reported outcomes with immediate-loaded two-implant-supported mandibular overdentures: Results of a 5-year prospective study - Yuriko Komagamine; Manabu Kanazawa; Daisuke Sato; Maiko Iwaki; Anna Miyayasu; Shunsuke Minakuchi (Elsevier, 2022)
Background/purpose: Few studies have comprehensively assessed long-term patient-reported outcomes for overdentures supported by two immediate implants. The purpose of the study was to evaluate patient-reported outcomes of immediately loaded two-implant-supported overdentures retained by ball attachments over a 5-year evaluation period. Material and methods: Nineteen participants with edentulous mandibles were provided with immediately loaded two-unsplinted-implant-supported overdentures retained by ball attachments. The participants completed the Japanese version of the Oral Health Impact Profile (OHIP)-EDENT-19 and the Patient's Denture Assessment (PDA). Additionally, patient satisfaction was measured by a 100-mm visual analog scale (VAS). Measurements were performed at baseline, and at 1 and 5 years following implant surgery. Results: Seventeen participants and 14 participants were evaluated at the 1-year and 5-year assessment, respectively. Considering the OHIP-EDENT-19, there was a significant decrease in the total (p = 0.046), "functional limitation" (p = 0.021), and "physical disability" (p = 0.034) scores at 1 year and the total (p = 0.045) and "physical disability" (p = 0.024) scores at 5 years following surgery, compared to the baseline scores. Considering the PDA, there was a significant increase in the "function" (p = 0.038) and "lower denture" (p = 0.003) scores at 1 year and the "function" (p = 0.032), "lower denture" (p = 0.008), and "esthetic and speech" (p = 0.043) scores at 5 years following surgery, compared to the baseline scores. Patient satisfaction at 1 year following surgery was significantly greater than that at baseline (p = 0.005). Conclusion: Immediately loaded two-unsplinted-implant-supported overdentures retained by ball attachments improved the oral health-related quality of life and self-assessment of dentures by the patients up to 5 years following implant surgery.